Selective Vulnerability of Cortical Border Zone to Microembolic Infarct. Issue 7 (July 2015) - Bergui, Mauro; Castagno, Davide; D'Agata, Federico; Cicerale, Alessandro; Anselmino, Matteo; Maria Ferrio, Federica; Giustetto, Carla; Halimi, Franck; Scaglione, Marco; Gaita, Fiorenzo
Abstract : Background and Purpose—: Endovascular procedures, including atrial fibrillation transcatheter ablation, may cause microembolization of brain arteries. Microemboli often cause small sized and clinically silent cerebral ischemias (SCI). These lesions are clearly visible on early postoperative magnetic resonance diffusion-weighted images. We analyzed SCI distribution in a population of patients submitted to atrial fibrillation transcatheter ablation. Methods—: Seventy-eight of 927 consecutive patients submitted to atrial fibrillation transcatheter ablation were found positive for acute SCI on a postoperative magnetic resonance. SCI were identified and marked, and their coordinates were transformed from native space into the International Consortium for Brain Mapping/Montreal Neurological Institute space. We then computed the voxel-wise probability distribution map of the SCI using the activation likelihood estimation approach. Results—: SCI were more commonly found in the cortex. In supratentorial regions, SCI selectively involved cortical border zone between anterior, middle, and posterior cerebral arteries; in infratentorial regions, distal territory of posteroinferior cerebellar artery. Possible explanations include selective embolization, linked to the vascular anatomy of pial arteries supplying those territories, reduced clearance of emboli in a relatively hypoperfused zone, or a combination of both. This particular distribution of lesions has been reported in both animal models and in patients with microemboli of different sources. Conclusions—: A selective vulnerability of cortical border zone to microemboli occurring during atrial fibrillation transcatheter ablation was observed. We hypothesize that such selectivity may apply to microemboli of different sources. Abstract : Supplemental Digital Content is available in the text.